Polycarbonyl hexaazatriphenylene derivatives and preparation methods and applications thereof

By developing polycarbonyl hexazabenzophenylade derivatives as the positive electrode material for aqueous zinc ion batteries, the environmental pollution and high raw material cost problems caused by transition metal elements in existing materials are solved, and high-performance and low-cost battery materials are achieved .

CN116253738BActive Publication Date: 2025-02-25CHANGZHOU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310039272.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-13
Publication Date
2025-02-25
Estimated Expiration
2043-01-13

AI Technical Summary

Technical Problem

The positive electrode materials of existing water-based zinc ion batteries contain transition metal elements, which have problems of environmental pollution and high raw material costs.

Method used

A polycarbonyl hexazabenzophenylade derivative was developed as a new positive electrode material. It has low cost, low energy consumption, high reproducibility and high yield through a simple synthesis process.

Benefits of technology

This material exhibits high discharge specific capacity, long-term cycle stability, excellent mechanical durability and flexibility in aqueous zinc ion batteries, and is suitable for large-scale energy storage devices and wearable electronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The present invention belongs to the field of synthesis of electrode materials, and specifically relates to a class of polycarbonyl hexaazatriphenylene derivatives and preparation methods and applications thereof. Under the protection of inert gas, hexaazatriphenylene hexacarboxylic acid trianhydride and ammonia water are added to a reactor and stirred at room temperature for dehydration condensation reaction; or hexaazatriphenylene hexacarboxylic acid trianhydride, 3,5-diamino-1,2,4-triazole and an organic solvent are added to the reactor, and after complete dissolution and uniform dispersion, the temperature is raised to reflux under stirring conditions, and a dehydration condensation reaction is carried out. After the reaction is completed, heating is stopped, ethanol is added for washing, and suction filtration is performed to synthesize polycarbonyl hexaazatriphenylene derivatives. The synthesized polycarbonyl hexaazatriphenylene derivatives are used for aqueous zinc ion battery positive electrode materials. The electrode material has good discharge specific capacity and excellent cycle stability, and has broad application prospects in large-scale energy storage devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of synthesis of electrode materials, and particularly relates to a polycarbonyl hexaazatriphenylene derivative and a preparation method and application thereof. Background Art

[0002] With the massive consumption of traditional non-renewable energy, it is now unable to meet the needs of human development. Therefore, finding renewable, clean and sustainable energy to replace existing traditional energy has become a top priority today. In order to meet sustainable development, safe, environmentally friendly, reliable and economical rechargeable battery technology is an ideal choice for portable electronic devices, electric vehicles and renewable power storage systems. For example, lithium-ion batteries, emerging metal ion batteries, etc., all have high energy density and long cycle life. However, lithium-ion batteries have problems such as high price of metallic lithium, low reserves, toxic electrolyte and safety, which seriously hinder their further large-scale energy storage applications. Therefore, the development of a low-cost, environmentally friendly and safe aqueous metal ion battery is a necessary trend.

[0003] Aqueous zinc-ion batteries (ZIBs) have a high theoretical capacity (820 mAh g -1 ) and volumetric capacity (5851 mAh cm -3 ), and the aqueous electrolyte it uses has good stability, can withstand large current density, and has a high overpotential in aqueous solution, and has gradually become one of the most promising new generation electrochemical energy storage devices. In addition, zinc reserves are relatively abundant on the surface (180 million tons) and the cost is relatively low. Combining the above advantages, aqueous zinc-ion batteries are considered to be one of the most promising aqueous metal-ion battery systems and are believed to be widely used in large-scale energy storage devices.

[0004] So far, the positive electrode materials of aqueous zinc-ion batteries that have been reported mainly include manganese compounds, vanadium compounds, Prussian blue compounds and organic compounds. However, these inorganic compounds contain toxic and harmful transition metal elements, which may cause serious environmental pollution problems when the batteries are discarded. Compared with inorganic materials containing transition metal elements, organic materials with redox activity stand out from many competitors. Organic compounds are mainly composed of elements such as C, H, O, N, S, etc., and have the characteristics of light weight, low cost, low toxicity, and sustainable utilization. In addition, the structure of organic synthesis products can be designed and adjusted, which provides more possibilities for the development and research of new organic positive electrode materials.

[0005] The research on organic cathode materials mainly focuses on (quinone) carbonyl compounds. Wang et al. proposed a new zinc-organic battery, dibenzo[b,i]thiophenequinone-5,7,12,14-tetraketone (DTT). The battery has a capacity of 210.9 mAh g -1 The high specific capacity of DTT / / Zn full battery can be cycled more than 23,000 times, which is far superior to the previously reported aqueous zinc batteries (Adv. Mater. 2020, 32, 2000338), but the cost of the raw materials used to synthesize it is relatively high. J. Fraser Stoddart et al. used triangular macrocyclic phenanthrenequinone (PQ-Δ) as the positive electrode material for aqueous rechargeable zinc ion batteries. The material has a high specific capacity of 30 mA g -1 The electric density is as high as 225 mAh g -1 Reversible capacity. 150mA g -1 At a higher current density, its reversible capacity is 210 mAh g -1 , and can be stably cycled 500 times without capacity decay, showing excellent electrochemical performance (J.Am.Chem.Soc.2020,142,2541-2548). However, the cost of the raw materials used to synthesize DTT and PQ-Δ is relatively high. In order to overcome these shortcomings, further improve the performance of organic cathode materials, and then improve the performance of aqueous zinc-ion batteries, it is still an important task to continuously develop and expand environmentally friendly and affordable organic cathode materials that can be applied in practical fields. Summary of the invention

[0006] The purpose of the present invention is to provide a class of polycarbonyl hexaazatriphenylene derivatives and their preparation methods and applications. The synthesis method of the present invention has simple process, low cost, good reproducibility and high yield. Such materials have broad application prospects in the field of aqueous zinc ion battery electrode materials.

[0007] In order to achieve the above-mentioned purpose, the technical solution adopted by the present invention is: a class of polycarbonyl hexaazatriphenylene derivatives, whose structural formula is:

[0008]

[0009] The preparation method of the above-mentioned polycarbonyl hexaazatriphenylene derivatives has the following reaction equation:

[0010]

[0011] The specific steps are as follows:

[0012] (1) Under the protection of inert gas, hexaazatriphenylene hexacarboxylic acid trianhydride and ammonia water are added to a reactor, and the reaction mixture is continuously stirred at room temperature to carry out a dehydration condensation reaction.

[0013] Alternatively, under the protection of inert gas, hexaazatriphenylene hexacarboxylic acid trianhydride, 3,5-diamino-1,2,4-triazole and an organic solvent are added to the reactor. After being fully dissolved and evenly dispersed, the reaction mixture is continuously stirred and the temperature is raised to reflux to carry out a dehydration condensation reaction.

[0014] The molar ratio of hexaazatriphenylene hexacarboxylic acid trianhydride to ammonia water is 1:2 to 1:9.

[0015] Alternatively, the molar ratio of hexaazatriphenylene hexacarboxylic acid trianhydride to 3,5-diamino-1,2,4-triazole is 1:1.5 to 1:6.

[0016] The organic solvent is 1-methyl-2-pyrrolidone (NMP) or N,N-dimethylformamide (DMF).

[0017] The dehydration condensation reaction time is 6-24 hours.

[0018] The inert gas is nitrogen or argon.

[0019] (2) After the reaction is completed, stop heating, cool to room temperature, filter, and wash with ethanol 2-3 times to obtain a polycarbonyl hexaazatriphenylene derivative material.

[0020] The above-mentioned polycarbonyl hexaazatriphenylene derivatives are used as positive electrode materials for aqueous zinc ion batteries.

[0021] Compared with the prior art, the present invention has the following advantages:

[0022] The polycarbonyl hexaazatriphenylene derivative of the invention has a simple synthesis process, is easy to operate, has low energy consumption, good reproducibility and excellent performance.

[0023] The polycarbonyl hexaazatriphenylene derivative material of the present invention can not only solve the problem of dissolution of naphthoquinone derivatives of organic materials into electrolytes, but also has high stability.

[0024] The polycarbonyl hexaazatriphenylene derivative material of the present invention is a new type of aqueous zinc battery positive electrode material with high discharge specific capacity, long-term cycle stability, high energy density and power density. More importantly, the aqueous strip zinc battery assembled with this type of material not only has high energy density and power density, but also has excellent mechanical durability and flexibility, and has broad application prospects in the field of aqueous zinc ion battery electrode materials and wearable electronic devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 is the infrared spectrum of hexaazatriphenylene hexacarboximide (compound A);

[0026] Figure 2 is the solid-state NMR of compound A1 H spectrum;

[0027] Figure 3 is the solid-state NMR of compound A 13 C spectrum;

[0028] Figure 4 is the mass spectrum of compound A;

[0029] Figure 5 Cyclic voltammograms of compound A button cell at different scan rates;

[0030] Figure 6 The cyclic voltammogram of the button cell of compound A at the same scan rate;

[0031] Figure 7 This is the rate stability diagram of compound A button cell;

[0032] Figure 8 This is the charge and discharge curve of compound A button cell at different current densities;

[0033] Fig. 9 Compound A button cell at 0.05A g -1 The charge and discharge curves at the current density of ;

[0034] Fig.10 This is the cycle stability diagram of compound A button cell;

[0035] Fig.11 The charge and discharge curves of compound A button cell at different active material loading ratios;

[0036] Fig.12 This is the solubility diagram of compound A button cell positive electrode material in the electrolyte;

[0037] Fig.13 This is the energy density and power density diagram of compound A button cell;

[0038] Fig.14 This is the assembly diagram of the flexible battery of compound A;

[0039] Fig.15 This is the rate stability diagram of compound A flexible battery;

[0040] Fig.16 This is the charge and discharge curve of compound A flexible battery at different current densities;

[0041] Fig.17 This is the charge and discharge curve of the flexible battery of compound A at the same current density;

[0042] Fig.18 This is the cycle stability diagram of the flexible battery of compound A;

[0043] Fig.19 This is the cycle stability diagram of compound A flexible battery at different folding angles;

[0044] Fig. 20 This is the charge and discharge curve of compound A flexible battery at different folding angles;

[0045] Fig.21 Energy density and power density diagram of compound A flexible battery.

[0046] Fig. 22 is the infrared spectrum of tris(3-amino-1,2,4-triazolyl)hexaazatriphenylene hexacarboximide (compound B);

[0047] Fig.23 is the solid-state NMR of compound B 1 H spectrum;

[0048] Fig.24 Liquid NMR of compound B 13 C spectrum;

[0049] Fig.25 is the mass spectrum of compound B;

[0050] Fig.26 Cyclic voltammograms of compound B button cell at different scan rates;

[0051] Fig. 27 The cyclic voltammogram of the button cell of compound B at the same scan rate;

[0052] Fig.28 This is the rate stability diagram of compound B button cell;

[0053] Fig.29 The charge and discharge curves of the button cell of compound B at different current densities;

[0054] Fig.30 Compound B button cell at 0.05A g -1 The charge and discharge curves at the current density of ;

[0055] Fig.31 This is the cycle stability diagram of compound B button cell;

[0056] Fig.32 The charge and discharge curves of the button cell of compound B at different active material loading ratios;

[0057] Fig.33 This is the solubility diagram of compound B button battery positive electrode material in the electrolyte;

[0058] Fig.34This is the energy density and power density diagram of compound B button cell;

[0059] Fig.35 This is the rate stability diagram of compound B flexible battery;

[0060] Fig.36 This is the charge and discharge curve of compound B flexible battery at different current densities;

[0061] Fig.37 This is the charge and discharge curve of the compound B flexible battery at the same current density;

[0062] Fig.38 This is the cycle stability diagram of the flexible battery of compound B;

[0063] Fig.39 This is the cycle stability diagram of compound B flexible battery at different folding angles;

[0064] Fig.40 This is the charge and discharge curve of compound B flexible battery at different folding angles;

[0065] Fig.41 Energy density and power density diagram of compound B flexible battery. DETAILED DESCRIPTION

[0066] The present invention is further described below by means of specific embodiments.

[0067] Example 1

[0068] In a 100mL three-necked flask, 30ml of ammonia water (28wt%) was added, and at the same time, hexaazatriphenylene hexacarboxylic acid trianhydride (purchased from Anaiji) (0.444g, 1mmol) was added. Under nitrogen protection, the reaction mixture was continuously magnetically stirred at room temperature for 6 hours. After the reaction, the solid was collected by vacuum filtration, washed three times with ethanol, and dried in vacuum at 60°C overnight to obtain compound A: hexaazatriphenylene hexacarboxylic acid trianide, with a yield of 85.8%. Figure 1 is the infrared spectrum, Figure 2 Solid-state NMR 1 H spectrum, Figure 3 Solid-state NMR 13 C spectrum, Figure 4 For the mass spectrum.

[0069] The active material of the electrode material is mixed and ground according to the mass ratio of active material: Ketjen black: binder (PVDF) = 30%: 60%: 10%, and then a dispersant (NMP) is added and ground, and then coated on a current collector titanium mesh or a stainless steel mesh, and vacuum dried at 80°C to form an electrode sheet. The electrode sheet is used as the positive electrode, the zinc sheet is used as the negative electrode, Celgard 2400 is used as the separator, and 2 mol·L -1 ZnSO4 was dissolved in distilled water as the electrolyte, assembled into button batteries and flexible batteries, and their electrochemical properties were investigated. Figure 5 Cyclic voltammograms of button cells at different scan rates; Figure 6 The cyclic voltammogram of the button cell at the same scan rate; Figure 7 This is the rate stability diagram of button cells; Figure 8 It is the charge and discharge curve of button battery at different current density; Fig. 9 For button cells at 0.05A g -1 The charge and discharge curves at the current density of ; Fig.10 This is the cycle stability diagram of the button battery; Fig.11 The charge and discharge curves of button batteries at different active material loading ratios; Fig.12 This is a comparison chart of the solubility of button battery positive electrode materials in electrolyte; Fig.13 Energy density and power density diagram for button cells; Fig.14 This is an assembly diagram of a flexible battery; Fig.15 This is the rate stability diagram of the flexible battery; Fig.16 This is the charge and discharge curve of the flexible battery at different current densities; Fig.17 This is the charge and discharge curve of the flexible battery at the same current density; Fig.18 This is the cycling stability diagram of the flexible battery; Fig.19 This is the cycle stability diagram of the flexible battery at different folding angles; Fig. 20 This is the charge and discharge curve of the flexible battery at different folding angles; Fig.21 Energy density and power density diagram of flexible batteries.

[0070] FT-IR(KBr,cm -1 ):3431,3126,2922,1625,1401,1109,790,614

[0071] 1 H NMR (400 MHz): δ: 7.62

[0072] 13 C NMR (400MHz): δ:136.33,151.68,168.27

[0073] ESI-MS m / z Calculated value: 441.02; Actual value: 464.3330, [M+Na] + .

[0074] Example 2

[0075] The preparation method is the same as that of Example 1, but the ratio of reactants is changed. When the molar ratio of hexaazatriphenylene hexacarboxylic acid trianhydride to ammonia water is 1:3, the yield is 83.2%.

[0076] Example 3

[0077] The preparation method is the same as that of Example 1, but the ratio of reactants is changed. When the molar ratio of hexaazatriphenylene hexacarboxylic acid trianhydride to ammonia water is 1:4, the yield is 86.7%.

[0078] Example 4

[0079] The preparation method is the same as that of Example 1, but the ratio of reactants is changed. When the molar ratio of hexaazatriphenylene hexacarboxylic acid trianhydride to ammonia water is 1:5, the yield is 80.2%.

[0080] Example 5

[0081] The preparation method is the same as that of Example 1, but the ratio of reactants is changed. When the molar ratio of hexaazatriphenylene hexacarboxylic acid trianhydride to ammonia water is 1:6, the yield is 82.7%.

[0082] Example 6

[0083] The preparation method is the same as that of Example 1, but the ratio of reactants is changed. When the molar ratio of hexaazatriphenylene hexacarboxylic acid trianhydride to ammonia water is 1:8, the yield is 86%.

[0084] Example 7

[0085] The preparation method is the same as that of Example 1, but the ratio of reactants is changed. When the molar ratio of hexaazatriphenylene hexacarboxylic acid trianhydride to ammonia water is 1:9, the yield is 89.3%.

[0086] Example 8

[0087] 45 mL of anhydrous DMF was added to a 100 ml three-necked flask and purged with nitrogen for 15 minutes, and hexaazatriphenylene hexacarboxylic acid trianhydride (0.444 g, 1 mmol) and 3,5-diamino-1,2,4-triazole (0.396 g, 4 mmol) were added at the same time. During the whole process, stirring was continued under nitrogen protection and heating reflux was continued for 24 hours, then the heating device was removed and cooled to room temperature, and the solid product was precipitated by ice water bath, the solid was collected by filtration, the filter cake was washed three times with ethanol, and vacuum dried to obtain compound B: tris (3-amino-1,2,4-triazolyl) hexaazatriphenylene hexacarboximide, with a yield of 75.2%. Fig. 22 is the infrared spectrum, Fig.23 Solid-state NMR1 H spectrum, Fig.24 Liquid NMR 13 C spectrum, Fig.25 For the mass spectrum.

[0088] The active material of the electrode material was used to make an electrode sheet according to the mass ratio of active material: Ketjen black: binder (PVDF) = 30%: 60%: 10%. The electrode sheet was used as the positive electrode, the zinc sheet was used as the negative electrode, Celgard 2400 was used as the separator, and 2 mol·L -1 ZnSO4 was dissolved in distilled water to make the electrolyte, which was assembled into button cells and flexible batteries, and their electrochemical properties were investigated. Fig.26 Cyclic voltammograms of button cells at different scan rates; Fig. 27 The cyclic voltammogram of the button cell at the same scan rate; Fig.28 This is the rate stability diagram of button cells; Fig.29 It is the charge and discharge curve of button battery at different current density;

[0089] Fig.30 For button cells at 0.05Ag -1 The charge and discharge curves at the current density of ; Fig.31 This is the cycle stability diagram of the button battery; Fig.32 The charge and discharge curves of button batteries at different active material loading ratios; Fig.33 This is a test chart of the solubility of button battery electrode materials in water; Fig.34 Energy density and power density diagram for button cells; Fig.35 This is the rate stability diagram of the flexible battery; Fig.36 This is the charge and discharge curve of the flexible battery at different current densities; Fig.37 This is the charge and discharge curve of the flexible battery at the same current density; Fig.38 This is the cycling stability diagram of the flexible battery; Fig.39 This is the cycle stability diagram of the flexible battery at different folding angles; Fig.40 This is the charge and discharge curve of the flexible battery at different folding angles; Fig.41 Energy density and power density diagram of flexible batteries.

[0090] FT-IR(KBr,cm -1 ):3431,2915,1632,1558,1380,1231,1103

[0091] 1 H NMR (400 MHz), δ: 5.47, 8.84

[0092] 13C NMR(CF3COOD,400MHz),δ:142.61,148.72,149.54,163.12,167.46

[0093] ESI-MS m / z Calculated value: 687.10; Actual value: 709.99, [M+Na] + .

[0094] Example 9

[0095] The preparation method is the same as that of Example 8, but the ratio of reactants is changed. When the molar ratio of hexaazatriphenylene hexacarboxylic acid trianhydride to 3,5-diamino-1,2,4-triazole is 1:1, the yield is 76.3%.

[0096] Example 10

[0097] The preparation method is the same as that of Example 8, but the ratio of the reactants is changed. When the molar ratio of hexaazatriphenylene hexacarboxylic acid trianhydride to 3,5-diamino-1,2,4-triazole is 1:2, the yield is 78.8%.

[0098] Embodiment 11

[0099] The preparation method is the same as that of Example 8, but the ratio of the reactants is changed. When the molar ratio of hexaazatriphenylene hexacarboxylic acid trianhydride to 3,5-diamino-1,2,4-triazole is 1:3, the yield is 74.3%.

[0100] Example 12

[0101] The preparation method is the same as that of Example 8, but the ratio of the reactants is changed. When the molar ratio of hexaazatriphenylene hexacarboxylic acid trianhydride to 3,5-diamino-1,2,4-triazole is 1:5, the yield is 70.1%.

[0102] Embodiment 13

[0103] The preparation method is the same as that of Example 8, but the ratio of the reactants is changed. When the molar ratio of hexaazatriphenylene hexacarboxylic acid trianhydride to 3,5-diamino-1,2,4-triazole is 1:6, the yield is 80.5%.

Claims

1. Application of a class of polycarbonyl hexaazatriphenylene derivatives, characterized in that: The derivative is used as a positive electrode material for an aqueous zinc ion battery, and the structure of the derivative is as follows: 。 2. A use of the polycarbonyl hexaazatriphenylene derivative as claimed in claim 1, characterized in that: The steps of the preparation method of the polycarbonyl hexaazatriphenylene derivative are as follows: (1) under the protection of inert gas, adding hexaazatriphenylene hexacarboxylic acid trianhydride and ammonia water into a reactor to carry out a stirring dehydration condensation reaction at room temperature; Alternatively, under the protection of an inert gas, hexaazatriphenylene hexacarboxylic acid trianhydride, 3,5-diamino-1,2,4-triazole and an organic solvent are added to a reactor, and after they are completely dissolved and evenly dispersed, the temperature is raised to reflux under stirring conditions to carry out a dehydration condensation reaction; (2) After the dehydration condensation reaction is completed, the heating is stopped, the mixture is cooled to room temperature, filtered, and washed with ethanol 2-3 times to obtain a polycarbonyl hexaazatriphenylene derivative.

3. The use of the polycarbonyl hexaazatriphenylene derivative according to claim 2, characterized in that: The organic solvent is 1-methyl-2-pyrrolidone or N,N-dimethylformamide.

4. The use of the polycarbonyl hexaazatriphenylene derivative according to claim 2, characterized in that: The dehydration condensation reaction time is 6-24 hours.

5. The use of the polycarbonyl hexaazatriphenylene derivative according to claim 2, characterized in that: The inert gas is nitrogen or argon.

Citation Information

Patent Citations

  • Organic luminescent material and preparation method and application thereof

    CN102659790B

  • Molecular templating of a surface

    US20050214471A1